AERODYNAMIC ANALYSIS OF FOLDING FIN AERIAL ROCKET 70 MM ON INCOMPRESSIBLE FLOW USING CFD-BASED SimScale - Dyah Rachmawati Berliet Haryadi; Edi Sofyan; Erwan Eko Prasetiyo (Sekolah Tinggi Teknologi Kedirgantaraan, 2023)
The rocket development process goes through several stages with the aim of ensuring rocket performance when simulated. One of the important stages in the rocket development process is knowing the aerodynamics on the rocket. Aerodynamics on rockets need to be known because they affect performance when the rocket is simulated. To obtain the results of aerodynamic analysis on rockets, analysis is needed on CM (Coefficient of Moment), CD (Coefficient of Drag), and CL (Coefficient Lift) prices. In this study, the object used was FFAR (Folding Fin Aerial Rocket) with a diameter of 70 mm. The aerodynamic analysis process is carried out through simulation with two software, namely SimScale and Datcom Missile. . The results of aerodynamic analysis on rockets by varying the time(s) and speed in simulations using SimScale showed quite convergent results with movements at Mach 0.1, 0.2, and 0.3 approaching each other. While the simulation results on the Datcom missile by varying the angle of attack (α) and speed also showed convergent results with movements at Mach 0.1, 0.2, and 0.3 approaching each other.